Effects of NonPharmacological Interventions on Dietary Practices, Energy Expenditure and Biochemical Parameters of Hypercholesterolemic Type 2 Diabetic Subjects - Afnan, Fadia; Saleh, Farzana; Mumu, Shirin Jahan; Akhter, Afroza; Ahmed, Kazi Rumana; Akter, Sanzida; Pervin, Tanjuma (Ibrahim Medical College Journal, 2010)
Nonpharmacological interventions play an important role in the management of diabetes and its complications. This study analyzed the effect of nonpharmacological interventions on dietary practices, energy expenditure and management outcome in terms of glycemic and lipidemic status of type 2 diabetic subjects with hypercholesterolemia. These interventions included dietary advice, leaflets, televised lectures, booklets, posters and a bimonthly publication in Bangla. Eighty newly diagnosed type 2 diabetic subjects (male: female ratio 47:33, age 46 ± 8 years) with hypercholesterolemia (fasting serum total cholesterol >200 mg/dl) were selected from BIRDEM by purposive sampling. The first interview was taken before any intervention while the second interview was taken after a minimum interval of 8 weeks. The daily intake of macro- and micro- nutrients was assessed by 24- hr recall method. Energy expenditure of the subjects was calculated by factorial method using physical activity level (WHO/FAO/UNU 1985). After intervention, the proportion of carbohydrate, protein and fat intake of the study subjects did not differ significantly compared to values before intervention. The daily intake of micronutrients also did not differ compared to those before intervention. No significant difference was found between pre and post intervention values of per day energy intake (kcal, 1621 ± 426 vs 1645 ± 623). Total energy expenditure after intervention was significantly higher (1649 ± 340) compared to before intervention (1519 ± 353, p<0.002). After intervention, fasting serum glucose level (7 ± 1.43 mmol/l), serum glucose 2 hrs after breakfast (11 ± 4.1 mmol/l) and total cholesterol (217 ± 35 mg/dl) were significantly reduced compared to before intervention values (9 ± 4, 16 ± 7, 231 ± 32 respectively; p=0.001 for FSG, p=0.001 for SGABF, p<0.001 for total cholesterol). Nonpharmacological intervention was found to be effective in improving the management of diabetes and its complications. Ibrahim Med. Coll. J. 2009; 3(2): 75-77 DOI: 10.3329/imcj.v3i2.4222